Tổng hợp và nghiên cứu phức chất hỗn hợp của một số đất hiếm với naphthoyltrifloaxeton và triphenylphotphin oxit - Nguyệt, Triệu Thị; Hiền, Đinh Thị; Hải, Nguyễn Minh; Huy, Nguyễn Hùng (Vietnam Journal of Chemistry, 2014)
Ternary complexes of rare earth metals Y, Pr, Sm, Eu, Tb, Ho with naphthoyl trifluoroacetone and triphenylphotphine oxide were prepared. IR and NMR spectroscopies were utilized for structural characterizations of the complex. The results confirmed that the coordinated water molecules were displaced by triphenylphotphine oxide and that the coordination of the central metal ion is through oxygen atoms of β-diketone ligand and oxygen atoms of triphenylphosphine oxide. Keywords: Rare earth, β-dixetone, luminescent materials, complexes.